LATEST EARLY-EARLIEST MIDDLE MIOCENE DEEP-SEA MOLLUSCS IN THE JAPAN SEA BORDERLAND - THE WARM-WATER HIGASHIBESSHO FAUNA IN TOYAMA PREFECTURE, CENTRAL JAPAN - Amano K.; Hamuro T.; Hamuro M. (My University, 2004)
Eighty-seven species of molluscs were obtained from the uppermost lower-lowest middle Miocene Higashibessho Formation at Shimo-sasahara, Yatsuo Town in Toyama Prefecture, central Japan. Among them, Pagodula shojii is new to science. Judging from the autochthonous species, the Higashibessho Formation was deposited at the lower sublittoral to upper bathyal depth. Both the deep-sea and the derived shallow-water species include many warm-water dwellers. During the latest early-earliest middle Miocene, the deep-sea species migrated from the Pacific side of central Honshu to the Japan Sea through deep-sea pathways.
Keywords: lower-lowest middle Miocene; deep-sea; Mollusca; Higashibessho Formation; Cenozoic::Neogene::Miocene; Кайнозой::Неоген::Миоцен